(untitled) (Journal of Mechanical Engineering, 2013)
Porous carbon materials have attracted interest recently as they are potential candidates for largenumber of applications especially in catalytic supports, battery electrodes, capacitors, gas storage and biomedicalengineering applications. As porous carbons are mostly amorphous in nature, a little presence of sp2 carbonstructure enhances the possibility of using these carbon materials for wider applications involving electricalconductivity. Electrical conductivity of in porous acitivated carbon is increased by doping a suitable metal ion. Ricehusk char is choosen in this study as precursor for preparation of conducting carbon. The produced conductingcarbon exibits p-type semiconductor in character when copper, nickle, zinc and silver ions are doped. The highestelectricaal conductivity of silver ion doped material is found to be 2.84x10-2 mho/cm at 60% of ion concentration ofdoping solution. The results of this study conclude that rice husk char could be used for producing conductingcarbon and silver ion is the better among other doping materials used. DOI: http://dx.doi.org/10.3329/jme.v43i1.15776